1985
DOI: 10.1063/1.865087
|View full text |Cite
|
Sign up to set email alerts
|

The influence of initial condition on the linear stability of time-dependent circular Couette flow

Abstract: The effect of the starting condition on the linear stability properties of circular Couette flow with a time-dependent inner-cylinder motion is investigated. In addition to the WKBJ approach employed previously by Eagles [Proc. R. Soc. London, Ser. A 355, 209 (1977)] for slowly varying flow, an initial-value method is also used. Results are presented for different stability criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Based on the relative condition of Chen et al [28], Kim et al [25] suggested that for the case of n=0.5, the relative instability condition be fullfiled at τ =τ c . If the related process is still diffusion dominant with Ma * =constant at τ =τ c , it is probable that Θ(τ, )=τ 1/2 Θ * (ζ ).…”
Section: Stability Equationsmentioning
confidence: 99%
“…Based on the relative condition of Chen et al [28], Kim et al [25] suggested that for the case of n=0.5, the relative instability condition be fullfiled at τ =τ c . If the related process is still diffusion dominant with Ma * =constant at τ =τ c , it is probable that Θ(τ, )=τ 1/2 Θ * (ζ ).…”
Section: Stability Equationsmentioning
confidence: 99%
“…For the case of negative ψ the Soret flux j S has a positive value. The boundary conditions have been obtained by the impermeable conditions for concentration at both boundaries, that is, j=0 at Z=0 and d. The above equations can be solved by using the Laplace transform: (13) where ζ=z/ . For the deep-pool system of small τ (Le≤τ≤0.01) the basic concentration field is approximated by (14) Here −c 0 (τ, 0)=c 0 (τ, 1)= .…”
Section: Governing Equationsmentioning
confidence: 99%
“…This condition is known as the strong stability criterion [2]. Neitzel [4] relaxed this strong stability criterion by considering the growth of the disturbance kinetic energy.…”
Section: -2 Energy Methodsmentioning
confidence: 99%
“…Here, we relax the above stability limits by introducing the relative stability concept: the temporal growth rate of the kinetic energy of the disturbance velocity should exceed that of the base velocity at the onset condition of secondary motion. This stability criterion was proposed by Chen et al [2], and applied into the various problems by Kim et al [6][7][8][9][10]. In the relative stability model the critical time τ r is determined, based on a most dangerous mode of instability:…”
Section: -2 Energy Methodsmentioning
confidence: 99%
See 1 more Smart Citation